Probability Distribution Fitting of Cost Overrun Profiles - Love, Peter; Sing, Michael; Wang, Xiangyu; Yung, Ping (RICS 2012, 2012)
The statistical characteristics of cost overruns experienced from contract award in 276 Australian construction and engineering projects were analysed. The skewness and kurtosis values of the cost overruns are computed to determine if the empirical distribution of the data follows a Normal distribution. The empirical distributions for the cost overruns are found to be non-Gaussian. Theoretical probability distributions are fitted to the cost overrun data. The Kolmogorov-Smirnov, Anderson-Darling and Chi-Squared non-parametric tests are used to determine the 'Goodness of Fit' of the selected probability distributions. A 3-Parameter Frechet probability function is found to describe the behaviour of cost overruns and provide the best overall distribution fit. The Frechet distribution is then used to calculate the probability of a cost overrun being experienced.